Deforestation Trends in the Congo Basin : Agriculture - Hourticq, Joel; Megevand, Carole; Tollens, Eric; Wehkamp, Johanna; Dulal, Hari (World Bank, Washington, DC, 2014)
The Congo Basin represents 70 percent of the African continent's forest cover and constitutes a large portion of Africa's biodiversity. Agricultural development is a central lever to help people out of poverty, as well as a key driver of deforestation. Forest-friendly agricultural development is a challenge for the region. This report describes some ways forest-friendly agricultural development can materialize in the Congo Basin. It is one of a series of reports prepared during a two-year attempt to analyze and better understand deforestation dynamics in the Basin. The report presents findings related to the agricultural sector in the Congo Basin and its potential impact on forest cover. It is based on an in-depth analysis of the sector, from previous trends through future prospects. It builds on results derived from a modeling exercise conducted by the International Institute for Applied Systems Analysis (IIASA) that scrutinized national, regional, and international trends in agricultural sectors and trade, and their impacts on Congo Basin forests. The structure of the report is as follows: chapter one gives an overview of the agricultural sector in the six countries, including an analysis of the sector's impact so far on forest cover; chapter two describes the prospects for development of agriculture in the near future and the potential impacts on forest under a business-as usual scenario; and chapter three identifies potential key levers in agricultural policy that can enable forest-friendly agriculture.